On the origin of European sheep as revealed by the diversity of the Balkan breeds and by optimizing population-genetic analysis tools - Ciani, Elena; Mastrangelo, Salvatore; Da Silva, Anne; Marroni, Fabio; Ferenčaković, Maja; Ajmone-Marsan, Paolo; Baird, Hayley; Barbato, Mario; Colli, Licia; Delvento, Chiara; Dovenski, Toni; Gorjanc, Gregor; et al. (My University, 2020)
In the Neolithic, domestic sheep migrated into Europe and subsequently spread in westerly and northwesterly directions. Reconstruction of these migrations and subsequent genetic events requires a more detailed characterization of the current phylogeographic differentiation.